Egalitarian norms can deflate identity-bias link in real-life groups - Sami Çoksan; Ahmed Faruk Sağlamöz (PLoS ONE, 2025)
Social identity theory posits that group membership influences individual behavior by fostering a sense of belonging and promoting normative conformity within groups. While much research has shown a link between ingroup identification and ingroup bias, the role of ingroup norms in moderating this association remains less explored. Specifically, how varying norms (egalitarianism vs. favoritism) affect bias in individuals with high ingroup identification requires further investigation. To address this gap, we examined whether ingroup norms alter the strength of the identification-bias relationship in two studies (N = 322). We investigated how non-WEIRD real-life group members’ ingroup bias was driven by their identification levels and perceived ingroup norm in Study 1 with a correlational design, and we experimentally manipulated ingroup norms in a simulated group discussion in Study 2. Both studies demonstrated that under a favoritism norm, participants with high ingroup identification showed greater ingroup bias, whereas this bias was deflated under an egalitarianism norm. However, contrary to our hypothesis, we did not find evidence that participants with high ingroup identification showed lower ingroup bias under the egalitarianism norm. We discuss these findings and suggest that fostering egalitarian norms within groups may reduce ingroup bias and discrimination, offering insight for interventions aimed at promoting intergroup harmony.